PENGARUH SISTEM INFORMASI KEUANGAN DAERAH, KONFLIK PERAN, DAN LINGKUNGAN PENGENDALIAN TERHADAP EFEKTIVITAS SISTEM PENGENDALIAN MANAJEMEN - Sri Paramita, Ni Nyoman; Budiartha, Ketut (E-Jurnal Akuntansi; Vol 8 No 2 (2014), 2014)
ABSTRACT Management control system is a process used to ensure that the resources dimililki by an entity has been used effectively and efficiently. This study aimed to examine the effect of regional financial information system, konflilk role and effectiveness of the control environment of the management control system. The population in this study were all civil servants who occupy part on education finance in Gianyar regency. The selection of the sample using purposive sampling technique and obtained as many as 125 respondents. The data analysis technique used is multiple linear regression analysis. The results of this study variables membuktukan that significant positive effect on the effectiveness of the management control system is a regional financial information system and control environment. While the variables that are significant negative effect of role conflict.
Keywords: Regional Finance Information System, Role Conflict, Environmental Control, Management Control System Effectiveness